Controlling salt and aroma perception through the inclusion of air fillers - Chiu, Natalie; Hewson, Louise; Yang, Ni; Linforth, Robert; Fisk, Ian D. (Elsevier, 2015)
Global dietary sodium consumption significantly exceeds the WHO recommended intake levels, although strategies are available for sodium reduction, most are partial product-specific solutions. A wider range of approaches is urgently required to enable food manufacturers to reduce sodium within processed foods. In this study, the addition of air inclusions within hydrogels has been evaluated for its ability to enhance the delivery of sodium and perception of saltiness and was shown, on a volume basis, to achieve an 80% reduction in total sodium with no loss of saltiness perception; the addition of a congruent aroma volatile was shown to enhance overall flavour perception in foamed systems. Air inclusions were shown to increase both the delivery and perception of salt and aroma, in addition to increasing overall flavour perception. This work will be of interest to both academic researchers in this field and industrialists looking for new approaches to mitigate loss of taste quality with sodium reduction.